Challenges for the Management in Creating a Better Work Environment: A Critical Evaluation of the Indian Jute Industry in the Post Liberalization Era - Srinivas Subba Rao, P.; Suseela Rani, P. (Prabandhan: Indian Journal of Management, 2012)
An incredible work environment is a place that promises to advance gifted employees and makes good on that promise. A healthy work environment provides people with opportunities to meet professional and personal goals. It is much more pleasurable, and less stressful to go to a work environment that is filled with positivity and enjoyment. A positive work environment is not only important for our physical, mental and emotional health, but is also important for the results that we produce for the organization that employs us. The better we feel at work, the more likely we will take pride in our job activities and be loyal to our organization. So, no organization is perfect without creating and maintaining a work environment of fairness, respect, and justice. The Indian Jute Industry is one of the oldest and high labour intensive industries, particularly unskilled and semi - skilled labour. This industry lost a huge number of man hours and productivity due to poor industrial relations. Various studies have revealed that industrial relations have improved in the post liberalization era in India. So, in the present study, the researchers analyzed the importance of the Work Environment in the Jute Industry in the post liberalization era. The study reveals that in the post liberalization era, a lot of changes occurred in the Work Environment (working conditions, work schedules, safety measures, etc.) of the jute industry. Time Period of the Study: July-October, 2011.